THE CHARACTERISTICS AND CHANGES OF BENTHIC RESOURCES IN NHA PHU WATERS, KHANH HOA PROVINCE - Ngai, Phan Duc; Tuan, Vo Si; Long, Nguyen Van; Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2016)
The characteristics and changes of benthic resources in Nha Phu waters, Khanh Hoa province were determined by data synthesis of previous studies and two field trips carried out in 2012 and 2015. The results have pointed out that the number of mollusc species (15 species) is 1.5 times higher than that of crustacean species but yield of crustacean always dominates (occupying 68 - 100% of the entire commercial yield of benthic animal). Therein, Portunus pelagicus (occupying 53 - 74% of the entire commercial yield of crustacean) and juvenile of lobsters Panulirus sppare dominant group. The majority of benthic resources are epifauna, inhabit subtidal zone, sandy bottom. Yield of benthic animal has decreased seriously. These changes were primarily caused by the reduction in mangrove area and the increase in the destructive fishing equipment such as the electric fishing and the box trap.